1992
DOI: 10.1063/1.462054
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and tunable far-infrared laser spectroscopy of the ammonia–water dimer

Abstract: Microwave and far-infrared spectra of the H, N-HOH dimer have been recorded from 36 to 86 GHz and 520 to 800 GHz with a planar supersonic jet/tunable laser sideband spectrometer. The a-type pure rotational microwave data extend the previous m = 0, K = 0 A symmetry manifold measurements of Herbine and Dyke [J. Chem. Phys. 83, 3768 ( 1980) ] to higher frequency and also provide an additional set of microwave transitions in the mK = + 1 E symmetry manifold. Two sets of five b-type rotation-tunneling bands, one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 51 publications
7
89
1
Order By: Relevance
“…The FT cavity can also scan only from 7 GHz to about 26 GHz, and even then the antenna must be manually adjusted to optimize the sensitivity from the lowest to the highest frequency. On the other hand, the Caltech planar supersonic jet/direct absorption microwave spectrometer, also described previously, 37,10 begins coverage at about 18 GHz and can reach up to 80 GHz. This machine has a much lower resolution of a few hundred kHz, but can scan quickly, up to 20 MHz/min or 1.2 GHz/h, allowing a broad, automated collection of data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FT cavity can also scan only from 7 GHz to about 26 GHz, and even then the antenna must be manually adjusted to optimize the sensitivity from the lowest to the highest frequency. On the other hand, the Caltech planar supersonic jet/direct absorption microwave spectrometer, also described previously, 37,10 begins coverage at about 18 GHz and can reach up to 80 GHz. This machine has a much lower resolution of a few hundred kHz, but can scan quickly, up to 20 MHz/min or 1.2 GHz/h, allowing a broad, automated collection of data.…”
Section: Methodsmentioning
confidence: 99%
“…The water-methanol dimer is the latest, and one of the most chemically complex, in a series of water-containing, hydrogen-bonded dimers studied in our laboratories by microwave and far-infrared spectroscopy, for the purpose of fitting the observed spectra to intermolecular potential energy surfaces ͑IPSs͒. [1][2][3][4][5][6][7][8][9][10][11] The complex formed between methanol and water is particularly interesting because both hydrophobic and hydrophilic forces contribute strongly to the IPS of this relatively small dimer, creating a high degree of anisotropy. In addition, the watermethanol dimer will provide a test of the adaptability of the IPSs of simpler dimers to larger, multi-functional interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations did not produce evidence for a transition state directly connecting 1 and 2: all attempts to calculate TS 12 collapse to TS 13 . This study also found that the transition state TS 11 corresponding to internal rotation of the NH 4 + unit of isomer 1 lies 13 kJ/mol above structure 1. On the basis of the error estimates arising from calculation of the exothermicities of reactions 1 and 2, the absolute error limits of these calculations were estimated to be (10 kJ/mol.…”
Section: Dft Calculationsmentioning
confidence: 54%
“…The first pathway involves isomerization within intermediate complex 1, DO‚‚‚DNH 3 + . In this case, internal rotation of the NH 3 D + unit in 1 exchanges the bridging hydrogen atom through TS 11 , lying 13 kJ/mol above the energy of 1. The second pathway proceeds through intermediate complex 2, D 2 O‚‚‚HNH 2 + , in which an internal rotation of the D 2 HO + unit to form DHO‚‚‚DNH 2 + precedes decay to products.…”
Section: Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation